(untitled) (International Journal of Studies in Nursing, 2017)
Background: Although patient rounds became part of the wards’ routine for many years, there are still gaps regarding its tasks, cyclicality and participants and also the round was not backed by clear goals or instructions. Aim: to examine how nurses perceive rounding in terms of its cyclicality, tasks and participants. Method: research participants were 181 nurses of the internal, surgery-orthopedic, and maternity wards. They fill a questionnaire containing 41 items, specifically designed for this research. Data was analyzed using descriptive and comparative statistics. Results: significant differences between nurses from the various wings (p=0.000) were found in the performance of actual rounding during all shifts. Rounding was performed in the internal wards every two hours and 48 minutes in average, compared with every two hours and 12 minutes in the surgery wards and every hour and 54 minutes in the maternity wards. A gaps were found between real and ideal (p=0.000), show the ideal timeframe between the rounds were shortened by 10-30 minutes in each shift. The tasks rated as most important in all shifts were: early identification of medical distress situations (respiratory, bleeding, changes in conciseness etc.), taking actions to avoid complications including identifying a malfunctioning transfusion, position changes, answering patient questions, pain assessment and treatment, and answering basic needs. Conclusions: A policy for the performance of rounding, may bridge the gap between real and ideal and promote the quality of nursing care will provide clear guidance as to its tasks, cyclicality and participants.